ESSENTIALS OF EXUDATIVE OTITIS MEDIA IMMUNOPATHOGENESIS AND PATHOPHYSIOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Based on statistical data, ear disorders are ranked second in terms of general otorhinolaryngological pathology, with only paranasal sinus and nose diseases ahead of them. Many forms of hearing loss arise in conjunction with most ear illnesses, affecting individuals not only during the acute stage of the illness but also in its chronic form. Given that over half of all patients with hearing loss are of working age, treating this illness is socially significant.